2015
DOI: 10.1007/s12529-015-9505-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Organizational Justice with Tinnitus and the Mediating Role of Depressive Symptoms and Burnout—Findings from a Cross-Sectional Study

Abstract: Organizational justice appeared inversely related to tinnitus and this association was explained by individual differences in burnout symptoms, suggesting mediation. Longitudinal studies may further help to strengthen the evidence base for prevention of tinnitus through promotion of organizational justice and prevention of burnout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…Our finding of a relationship between bothersome tinnitus and burnout is consistent with the results of a cross-sectional study by Hébert et al (2012), who report that emotional exhaustion (which is part of the burnout symptomatology) is a predictor of tinnitus severity. In addition, Herr et al (2016) found that burnout mediates the effects of work-related stress (low organizational justice) on tinnitus. However, we only found an effect of burnout in the moderation analysis, but not in the multivariable adjusted regression analysis.…”
Section: Clear Associations With Bothersome Tinnitusmentioning
confidence: 99%
“…Our finding of a relationship between bothersome tinnitus and burnout is consistent with the results of a cross-sectional study by Hébert et al (2012), who report that emotional exhaustion (which is part of the burnout symptomatology) is a predictor of tinnitus severity. In addition, Herr et al (2016) found that burnout mediates the effects of work-related stress (low organizational justice) on tinnitus. However, we only found an effect of burnout in the moderation analysis, but not in the multivariable adjusted regression analysis.…”
Section: Clear Associations With Bothersome Tinnitusmentioning
confidence: 99%
“…In another study, workplace fairness was a strong predictor of emotional exhaustion among male and female police in Nigeria [27]. In addition, perceived unfairness at work has been shown to predict depression and burnout [28]. As for rewards, instead of being linked to value as in the original model, we proposed a relationship between rewards and exhaustion.…”
Section: Causal Model Of Burnoutmentioning
confidence: 99%
“…Moreover, lack of OJ is one of the psychosocial work factors that were associated with suicidality among Finnish anaesthesiologists [47]. Procedural justice and interactional justice were associated with tinnitus (the perception of a sound while an external source is absent) in German pharmaceutical employees [48].…”
Section: Physical Health 14mentioning
confidence: 99%